Multiplicity Results for Variable-Coefficient Singular Third-Order Differential Equation with a Parameter - Zhibo Cheng; Yun Xin (Abstract and Applied Analysis)
We investigate a class of variable coefficients singular third-order differential equation with superlinearity or sublinearity assumptions at infinity for an appropriately chosen parameter. By applications of Green’s function and the Krasnoselskii fixed point theorem, sufficient conditions for the existence of positive periodic solutions are established.